Against Person Essentialism. Issue 515 (29th June 2020) - Olson*, Eric T; Witt, Karsten
Abstract: It is widely held that every person is a person essentially, where being a person is having special mental properties such as intelligence and self-consciousness. It follows that nothing can acquire or lose these properties. The paper argues that this rules out all familiar psychological-continuity views of personal identity over time. It also faces grave difficulties in accounting for the mental powers of human beings who are not intelligent and self-conscious, such as foetuses and those with dementia.